Meconium pseudocyst secondary to ileal atresia complicated by volvulus: antenatal MR demonstration - Šimonovský, Václav; Lisý, Jiří (Pediatric radiology, 2007)
We report a case of meconium pseudocyst evaluated by prenatal MR imaging. The unusual features were its huge size, the absence of meconium peritonitis, and its development late in fetal life. The case also demonstrates a possible diagnostic pitfall since it suggests that rapid deterioration of a mechanically compensated bowel obstruction may occur, potentially occurring only after an MRI study has been performed.
Keywords: dospělí; Magnetic Resonance Imaging; mekonium; Ileum; nemoci plodu; Cysts; Female; novorozenec; ileum; Adult; Intestinal Volvulus; ženské pohlaví; Meconium; Fetal Diseases; prenatální diagnóza; lidé; Infant, Newborn; novorozenec nedonošený; magnetická rezonanční tomografie; těhotenství; Prenatal Diagnosis; cysty; Infant, Premature; volvulus intestini; Intestinal Atresia; Ultrasonography, Prenatal; atrézie střev; Pregnancy; ultrasonografie prenatální; Humans